2019
DOI: 10.1055/s-0038-1677008
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Management of Epilepsy and Seizures

Abstract: Seizure- and epilepsy-related complications are a common cause of emergency medical evaluation, accounting for 5% of 911 calls and 1% of emergency department visits. Emergency physicians and neurologists must be able to recognize and treat seizure- and epilepsy-related emergencies. This review describes the emergency evaluation and management of new onset seizures, breakthrough seizures in patients with known epilepsy, status epilepticus, acute symptomatic seizures, and acute adverse effects of antiepileptic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 81 publications
(78 reference statements)
0
2
0
1
Order By: Relevance
“…An erster Stelle des Behandlungsablaufs (▶ Abb. 1) steht das Erheben und Stabilisieren der Vitalparameter [17]. Falls Schockraumkriterien erfüllt sind, wird anhand des entsprechenden konservativen Schockraumprotokolls behandelt [18,19].…”
Section: Initiales Assessmentunclassified
“…An erster Stelle des Behandlungsablaufs (▶ Abb. 1) steht das Erheben und Stabilisieren der Vitalparameter [17]. Falls Schockraumkriterien erfüllt sind, wird anhand des entsprechenden konservativen Schockraumprotokolls behandelt [18,19].…”
Section: Initiales Assessmentunclassified
“…Epileptic seizures constitute a significant portion of patient presentations to the emergency department. It has been reported that 5% of emergency calls are due to epileptic seizures [2].…”
Section: Introductionmentioning
confidence: 99%
“…Immediate therapeutic intervention is required to minimize the risk of shortand long-term morbidity. Delayed treatment increases the risk of a self-sustained seizure and pharmacologic failure (Altered Mental Status (AMS) [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%